Pengaruh Fear of Missing Out dan Desain Produk serta Harga terhadap Keputusan Pembelian Produk MINISO Samarinda - Julianti Puji Rahmi Handayani Sabri; Alexander Sampeliling (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the influence of fear of missing out (FOMO), product design, and price on purchasing decisions for MINISO products in Samarinda. The research employed a quantitative approach with a purposive sampling technique. Data were collected through a questionnaire distributed to 100 respondents who had made purchases at MINISO. The data were analyzed using multiple linear regression with the assistance of Statistical Package for the Social Sciences (SPSS) version 25, supported by instrument testing, classical assumption testing, and hypothesis testing. The results indicate that fear of missing out, product design, and price have a positive and significant effect on purchasing decisions, with a significance value of 0.000 < 0.05. Simultaneously, the three variables significantly influence purchasing decisions with an F-value of 28.654 and a coefficient of determination (R²) of 0.472, indicating that 47.2% of purchasing decisions are influenced by these variables, while the remaining 52.8% are affected by other factors beyond the scope of this study. The study concludes that price is the strongest factor influencing purchasing decisions; therefore, companies need to implement pricing strategies aligned with product value and quality to strengthen competitiveness and enhance consumer purchasing decisions.